Silvicultura de precisão aplicada ao desenvolvimento de eucalyptus ssp no estado do Tocantins - Ferreira Júnior, José Moisés (Universidade Federal do Tocantins, 2019)
In the quest for efficiency in the use of natural resources due to the constant increase in world demand, geostatistics appears as an important tool to achieve this objective. The objective of this work was to determine the spatial variability of soil chemical attributes in the Eucalyptus ssp. Silviculture system. in the southern region of the State of Tocantins and to help determine the nutritional deficiency and the best form of soil management.The research was carried out at Fazenda Recanto da Serra, a municipality of Brejinho in the Tocantins state(11°01'03"S and 48°34'04"W,) 244 m of altitude. (average, median, minimum, and maximum), variability (coefficient of variation) and central tendency (asymmetry, and kurtosis) were determined. and semivariogram adjustment. The data was normal, finding spatial dependence of the data, generating the maps of isolines and allowing the visual identification of the zones with the greatest deficits. Although being managed for several years, the soil of Fazenda Recanto da Serra shows heterogeneity regarding fertility classes in different parts of its area. With the best knowledge about the spatial variability of each element in the area, acquired through geostatistics, it is possible to reduce fertilizer application costs when compared to the conventional method where an average is assumed and is incorporated throughout the area.